2013
DOI: 10.4172/2161-1076.s12-001
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology of Palpable Breast Lump: A Study of 1778 Cases

Abstract: Background: Breast carcinoma is the most common malignant tumour and the leading cause of death from cancer in women. A large number of patients in Bangladesh have been suffering from breast cancer. Now-a-days, FNAC is being performed as a pre-operative test to evaluate breast lump. FNAC is cost effective and can prevent unnecessary surgery. As FNAC became more reliable in diagnosing malignancy and thereby the use of frozen-section histology had been reduced by about 80%. This study intended to look the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The mean age for malignant cases was 43.24±14.45 years. [1,2,3,4,5,8,9,11,12,13] In the present study, 90 cases were positive for malignancy (17.5%). 04 cases (0.78%) were categorized into Atypical Ductal Hyperplasia (ADH)/Ductal Carcinoma in Situ (DCIS) and 05 cases were classified as suspicious of malignancy (0.97%).…”
Section: Resultssupporting
confidence: 46%
See 3 more Smart Citations
“…The mean age for malignant cases was 43.24±14.45 years. [1,2,3,4,5,8,9,11,12,13] In the present study, 90 cases were positive for malignancy (17.5%). 04 cases (0.78%) were categorized into Atypical Ductal Hyperplasia (ADH)/Ductal Carcinoma in Situ (DCIS) and 05 cases were classified as suspicious of malignancy (0.97%).…”
Section: Resultssupporting
confidence: 46%
“…Similar results regarding the percentage of cases positive for malignancy have been reported in various other studies. [1,2,4,5,9,11,12,13,14] 38 of 90 cases classified as malignant showed enlarged and palpable axillary lymph nodes. 09 (10%) of these cases showed metastatic deposits whereas 29 (32.2%) showed reactive changes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study from Bangladesh found it to be 44.3 years. 30 In India, a number of hospital-based studies found mean age to be 44.2 years to 49.6 years. 31 Mean age in Pakistani studies ranged from 45 to 50 years.…”
Section: Discussionmentioning
confidence: 99%